Protective Role of Surfactant Protein-D Against Lung Injury and Oxidative Stress Induced by Nitrogen Mustard. (30th July 2018) - Sunil, Vasanthi R; Vayas, Kinal N; Cervelli, Jessica A; Ebramova, Elena V; Gow, Andrew J; Goedken, Michael; Malaviya, Rama; Laskin, Jeffrey D; Laskin, Debra L
Abstract: Nitrogen mustard (NM) is a vesicant known to cause acute pulmonary injury which progresses to fibrosis. Macrophages contribute to both of these pathologies. Surfactant protein (SP)-D is a pulmonary collectin that suppresses lung macrophage activity. Herein, we analyzed the effects of loss of SP-D on NM-induced macrophage activation and lung toxicity. Wild-type (WT) and SP-D −/− mice were treated intratracheally with PBS or NM (0.08 mg/kg). Bronchoalveolar lavage (BAL) fluid and tissue were collected 14 days later. In WT mice, NM caused an increase in total SP-D levels in BAL; multiple lower molecular weight forms of SP-D were also identified, consistent with lung injury and oxidative stress. Flow cytometric analysis of BAL cells from NM treated WT mice revealed the presence of proinflammatory and anti-inflammatory macrophages. Whereas loss of SP-D had no effect on numbers of these cells, their activation state, as measured by proinflammatory (iNOS, MMP-9), and anti-inflammatory (MR-1, Ym-1) protein expression, was amplified. Loss of SP-D also exacerbated NM-induced oxidative stress and alveolar epithelial injury, as reflected by increases in heme oxygenase-1 expression, and BAL cell and protein content. This was correlated with alterations in pulmonary mechanics. In NM-treated SP-D −/−, but not WT mice, there was evidence of edema, epithelial hypertrophy and hyperplasia, bronchiectasis, and fibrosis, as well as increases in BAL phospholipid content. These data demonstrate that activated lung macrophages play a role in NM-induced lung injury and oxidative stress. Elucidating mechanisms regulating macrophage activity may be important in developing therapeutics to treat mustard-induced lung injury.